Dynamical coherence of specially absolutely partially hyperbolic endomorphisms on T2. (12th April 2019) - He, Baolin; Shi, Yi; Wang, Xiaodong
Abstract: In this paper, we prove that every specially absolutely partially hyperbolic endomorphism f on is dynamically coherent. The key point is that we rule out Reeb components in the unstable foliation of f . Moreover, we exhibit a specially partially hyperbolic endomorphism on, which preserves a Reeb foliation as unstable foliation and is not dynamically coherent.